The Effect Of Alternative Relaxation Aromatherapy On Labour Pain - Hetty A Panggabean; Juana Linda Simbolon; Emilia Silvana Sitompul (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Childbirth is a natural process and every mother has the right to receive safe and satisfactory services. Pain, anxiety and fatigue accumulate during labor, causing increased release of catecholamine and steroid hormones that result in decreased uterine contractions, reduced blood flow and oxygen to the uterus, resulting in uterine ischemia which results in increased pain impulses. Midwives need to develop strategies in this regard. Lemon aromatherapy contains limonene compounds that can inhibit the prostaglandin system. The scent of lemon can stimulate endorphins that function as pain relievers and make mothers happy. This study aimed to examine the impact was to analyze the effect of aromatherapy on labor pain with experimental pre and post test and control group design research types. The number of samples in this study was 34 mothers in labor consisting of 17 intervention groups and 17 control groups. This study used the Mann-Whitney test to analyze with a 95% confidence level. The results of this study showed a significant difference in pain levels in mothers who received aromatherapy and did not receive aromatherapy: p value 0.006 <0.05. Conclusion: There is an effect of aromatherapy on the level of pain in the first stage of labor in the active phase. Suggestion: Providing lemon aromatherapy to mothers in labor can be an option to reduce pain levels. This can also develop non-pharmacological therapeutic midwifery care.